2012
DOI: 10.1128/aac.05104-11
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of the Fosfomycin Resistance Gene fosA3 with CTX-M β-Lactamase Genes and rmtB Carried on IncFII Plasmids among Escherichia coli Isolates from Pets in China

Abstract: The presence and characterization of plasmid-mediated fosfomycin resistance determinants among Escherichia coli isolates collected from pets in China between 2006 and 2010 were investigated. Twenty-nine isolates (9.0%) were positive for fosA3, and all of them were CTX-M producers. The fosA3 genes were flanked by IS26 and were localized on F2:A؊:B؊ plasmids or on very similar F33:A؊:B؊ plasmids carrying both bla CTX-M-65 and rmtB. These findings indicate that the fosA3 gene may be coselected by antimicrobials o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
139
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 26 publications
8
139
6
Order By: Relevance
“…This indicated that both horizontal gene transfer and clonal spread were responsible for the dissemination of the rmtB gene in the E. coli strains in this study. The prevalence of plasmids carrying rmtB has frequently been observed to be associated with the incompatibility group F (IncF) in humans and other animals in China (Yu et al, 2010;Hou et al, 2012), and with IncA/ C in humans and IncF in companion animals in Korea (Kang et al, 2008;So et al, 2012). However, all rmtB-carrying plasmids in the present study belonged to IncI1.…”
Section: Transfer Of Aminoglycoside Resistance and Plasmid Replicon Tcontrasting
confidence: 50%
See 1 more Smart Citation
“…This indicated that both horizontal gene transfer and clonal spread were responsible for the dissemination of the rmtB gene in the E. coli strains in this study. The prevalence of plasmids carrying rmtB has frequently been observed to be associated with the incompatibility group F (IncF) in humans and other animals in China (Yu et al, 2010;Hou et al, 2012), and with IncA/ C in humans and IncF in companion animals in Korea (Kang et al, 2008;So et al, 2012). However, all rmtB-carrying plasmids in the present study belonged to IncI1.…”
Section: Transfer Of Aminoglycoside Resistance and Plasmid Replicon Tcontrasting
confidence: 50%
“…The rmtB gene is located between the Tn2 transposon and insertion elements such as IS26, ISCR1 and ISCR3 (Doi et al, 2008;Du et al, 2009). Recently, the rmtB gene has often been found to coexist with bla CTX-M and fosA3 (Hou et al, 2012;Lee et al, 2012;Sun et al, 2012;Pan et al, 2014), which could pose a threat to animal husbandry and public health. The dissemination of plasmids carrying rmtB has frequently been observed to be associated with the IncF and IncA/C incompatibility groups (Kang et al, 2008;Yu et al, 2010;Hou et al, 2012), whereas IncI1 plasmids harbouring rmtB are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In China, plasmid-mediated fosfomycin resistance has been frequently detected among CTX-M-producing isolates in animals (10,34). It was unexpected, since the use of fosfomycin in foodproducing animals is not approved in China.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the presence of fosfomycin resistance genes, along with various ␤-lactamases, including the AmpC-like and extendedspectrum ␤-lactamases (6,10). In this study, we characterized a newly identified fosA7 gene that confers resistance to fosfomycin in Salmonella Heidelberg strains isolated from broiler chickens.…”
mentioning
confidence: 99%